Japanese industrial relations interface in the Philippines - Agamon, Marie E.; Amante, Maragtas S. V..; Ofreneo, Rene E.. (Quezon City : U. P. Solair, 1992)
In cooperation with Japan Research team
Keywords: Industrial relations; Japan-Foreign economic relations -- Philippines; Philippines -- Foreign economic relations -- Japan